Stability of succinylcholine solutions stored at room temperature studied by nuclear magnetic resonance spectroscopy. Issue 3 (9th March 2007) - Adnet, Frederic; Le Moyec, Laurence; Smith, Charles E; Galinski, Michel; Jabre, Patricia; Lapostolle, Frederic
Abstract : The effect of storage temperature on the stability of two succinylcholine chloride solutions (20 and 50 mg/ml) was evaluated. Molecular composition was analysed using nuclear magnetic resonance spectroscopy. At room temperature, the degradation rate constant was 1.2%/month for the 20 mg/ml solution and 2.1%/month for the 50 mg/ml solution. The corresponding monthly degradation rates for the two solutions were 0.18% and 0.30% when stored at 4°C, and 5.4% and 8.1% when stored at 37°C. If a 10% loss of potency is considered acceptable, then the 20 and 50 mg/ml succinylcholine solutions can be stored in emergency resuscitation carts at room temperature for 8.3 and 4.8 months, respectively.